Sequence‐Based Prediction of Promiscuous Acyltransferase Activity in Hydrolases. Issue 28 (11th May 2020) - Müller, Henrik; Becker, Ann‐Kristin; Palm, Gottfried J.; Berndt, Leona; Badenhorst, Christoffel P. S.; Godehard, Simon P.; Reisky, Lukas; Lammers, Michael; Bornscheuer, Uwe T.
Abstract: Certain hydrolases preferentially catalyze acyl transfer over hydrolysis in an aqueous environment. However, the molecular and structural reasons for this phenomenon are still unclear. Herein, we provide evidence that acyltransferase activity in esterases highly correlates with the hydrophobicity of the substrate‐binding pocket. A hydrophobicity scoring system developed in this work allows accurate prediction of promiscuous acyltransferase activity solely from the amino acid sequence of the cap domain. This concept was experimentally verified by systematic investigation of several homologous esterases, leading to the discovery of five novel promiscuous acyltransferases. We also developed a simple yet versatile colorimetric assay for rapid characterization of novel acyltransferases. This study demonstrates that promiscuous acyltransferase activity is not as rare as previously thought and provides access to a vast number of novel acyltransferases with diverse substrate specificity and potential applications. Abstract : What's the score? Promiscuous acyltransferase activity of esterases strongly correlates with active‐site hydrophobicity. A hydrophobicity scoring concept was developed that enables the accurate prediction of promiscuous acyltransferase activity simply from the amino acid sequence of the enzyme cap domain.